2013
DOI: 10.1172/jci65634
|View full text |Cite
|
Sign up to set email alerts
|

Atrx deficiency induces telomere dysfunction, endocrine defects, and reduced life span

Abstract: Human ATRX mutations are associated with cognitive deficits, developmental abnormalities, and cancer. We show that the Atrx-null embryonic mouse brain accumulates replicative damage at telomeres and pericentromeric heterochromatin, which is exacerbated by loss of p53 and linked to ATM activation. ATRX-deficient neuroprogenitors exhibited higher incidence of telomere fusions and increased sensitivity to replication stressinducing drugs. Treatment of Atrx-null neuroprogenitors with the G-quadruplex (G4) ligand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
142
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(154 citation statements)
references
References 94 publications
11
142
0
1
Order By: Relevance
“…Loss of ATRX leads to centromere instability and aneuploidy in mouse oocytes and preimplantation embryos (Baumann et al 2010). ATRX deficiency by conditional knockouts in neuronal cell lineages or RNAi knockdown in cultured cells induced cell death, telomere dysfunction, and prolonged mitosis, with defects including anaphase bridges and lagging chromosomes (Ritchie et al 2008;Watson et al 2013). These are the same defects that we observed in the H3.3 knockout MEFs.…”
Section: Discussionsupporting
confidence: 74%
“…Loss of ATRX leads to centromere instability and aneuploidy in mouse oocytes and preimplantation embryos (Baumann et al 2010). ATRX deficiency by conditional knockouts in neuronal cell lineages or RNAi knockdown in cultured cells induced cell death, telomere dysfunction, and prolonged mitosis, with defects including anaphase bridges and lagging chromosomes (Ritchie et al 2008;Watson et al 2013). These are the same defects that we observed in the H3.3 knockout MEFs.…”
Section: Discussionsupporting
confidence: 74%
“…It is thus notable that Bmi1-deficient mice show reduced lifespan, genomic instability, neurodegeneration, and progeria features (38,(42)(43)(44)(45)75). Similar anomalies were also reported for ATRxdeficient mice (18,20). Taken together, this raises the possibility that BMI1 requirement for constitutive heterochromatin formation and silencing could underlie the premature aging/ senescence and genomic instability phenotypes observed in Bmi1-null mice and cells.…”
Section: Ink4asupporting
confidence: 81%
“…ATRX enrichment has been previously reported at subtelomeres and telomeres of human primary cells and mouse embryonic stem cells (37,38). More recently, Atrxnull mouse embryonic brain cells were shown to exhibit telomeric damage that could be worsened by treatment with the G-quadruplex ligand telomestatin, suggesting a role for ATRX in the replication of telomeric G4-DNA structures (39). In mouse embryonic stem cells, ATRX and H3.3 colocalized within PML bodies containing telomeric DNA (40).…”
Section: Discussionmentioning
confidence: 80%
“…Alternatively, the present, as well as the recent (35), findings that ATRX inactivation diminished TERRA levels might be explained by the occurrence of a concomitant loss of control of histone/DNA methylation at the subtelomeres. Indeed, in mouse embryonic stem cells, disruption of ATRX/H3.3 binding led to a loss of control of the telomeric histone methylation pattern (39), and in human cells, TERRA abundance is negatively regulated by methylation of TERRA promoter CpG islands (41). Of note, it was recently reported that genetic inactivation of ATRX led to persistence of both TERRA and RPA foci at telomeres of HeLa cells in G 2 /M, suggesting a role for ATRX in cell cycle-dependent regulation of TERRA abundance at telomeres (42).…”
Section: Discussionmentioning
confidence: 99%